Kutukan dan berkah dalam cerita Jawa Kuna; Sebuah refleksi sikap arogan para pemilik kekuasaan - Retno, Dwi Woro (UI Scholars Hub, 2005)
Old Javanese tales like Adiparwa and Sudamala are full of elements of curse cast by a man or a god. The curses take the form of words uttered full of emotion and anger to the addressee. Curses may result in a physical transformation or a change in the fate of the person cursed. A curse cast by a god demonstrates the power. A curse, however, eventually produces blessing. Curse and blessing are two things that are different from and opposite to one another.